Duration of Gadget Use with Development Level of Five Year Old Children in Pembina State Kindergarten, Southwest Aceh Regency - Andriani, Rika; Rosita, Erlia; Tiara, Anita; Zakiyah, Zakiyah; Sari, Mirda (Journal of Midwifery and Nursing, 2024)
Information technology is becoming a human consumption nowadays, many children use gadgets to play, watch videos and learn via gadgets. Using gadgets to access various sites and without parental supervision will have an impact on children's development. This type of research uses observational analytics with a cross sectional study approach. The sample in the research was 70 people with the sampling technique namely total sampling. Data were analyzed using Chi Square. The research results show that there is a relationship between the duration of gadget use and development with a p-value of 0.000. The use of gadgets by children must be controlled by parents so that they do not have a negative impact on children, especially on child development